Pioglitazone Reduces Hepatocellular Carcinoma Development in Two Rodent Models of Cirrhosis - Li, Shen (J Gastrointest Surg, 2018)
BACKGROUND: Hepatocellular carcinoma (HCC) is one of the deadliest malignancies worldwide due to the lack of effective treatments. Chemoprevention in high-risk patients is a promising, alternative strategy. In this study, pioglitazone was investigated for its ability to prevent hepatocarcinogenesis in two rodent models of cirrhosis. METHODS: In the first model, male Wistar rats were given repeated, low-dose injections of diethylnitrosamine (DEN) to accurately recapitulate the progression of fibrosis to cirrhosis and HCC. In the second model, a single dose of DEN was administered to male C57Bl/6 pups at day fifteen followed by administration of a choline-deficient, L-amino acid defined, high-fat diet (CDAHFD) at week six for 24 weeks. Pioglitazone treatment started at the first signs of fibrosis in both models. RESULTS: Pioglitazone effectively reduced fibrosis progression and HCC development in both models. Gross tumor nodules were significantly reduced after pioglitazone treatment (7.4 ± 1.6 vs. 16.6 ± 2.6 in the rat DEN model and 5.86 ± 1.82 vs. 13.2 ± 1.25 in the mouse DEN+CDAHFD model). In both models, pioglitazone reduced the activation of mitogen-activated protein kinase (MAPK) and upregulated the hepato-protective AMP-activated protein kinase (AMPK) pathway via increasing circulating adiponectin production. CONCLUSION: Pioglitazone is an effective agent for chemoprevention in rodents and could be repurposed as a multi-targeted drug for delaying liver fibrosis and hepatocarcinogenesis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11605-018-4004-6) contains supplementary material, which is available to authorized users.